Outlook 2016 for dummies - Dyszel, Bill (--For dummies., 2016)
Be more productive and simplify your life with Outlook 2016! Ever feel like you're drowning in your inbox? Outlook 2016 For Dummies helps you lower the metaphorical water levels by quickly prioritizing incoming email. Instead of wading through messages and tasks all day, use Outlook as it was intended as a productivity tool to organize your tasks on the to-do bar, filter junk email, make the most of Outlook's anti-phishing capabilities, manage email folders, use smart scheduling tools, leverage RSS support, collect electronic business cards, and integrate your Microsoft OneNote, Project, Access, and SharePoint files. This book is updated to reflect the latest and greatest features integrated into the Outlook 2016 user interface to ensure you're at the top of your Outlook game. With over 1.1 billion users worldwide and 90% market share for productivity suites, a figure that roughly translates into one in seven people the world over, odds are you'll need to learn how to use Microsoft Office programs including Outlook if you want to excel in the workplace.